Analysis of Challenges and Difficulties of Undergraduate Students of Tadris Mathematics Uin K.H Abdurrahman Wahid Pekalongan in A Complex Analysis Course Reviewed from Learning Anxiety - Setiawan, Arif; Ghofar, Muhammad Abyyu; Salisa, Sabina Es; Mahmudah, Umi (Jurnal Pendidikan Sultan Agung, 2024)
Complex analysis is a branch of mathematical analysis that focuses on the study of complex number functions, where the complex number functions is one of the main topics of discussion. This article aims to describe the challenges and difficulties of Tadris Mathematics students at UIN K.H. Abdurrahman Wahid Pekalongan in understanding complex number functions material seen from learning anxiety. This research uses a descriptive qualitative approach. The subjects of this research were 32 Tadris Mathematics students who were taking complex analysis courses in the 2023/2024 academic year. Data collection techniques used interviews and observations of 32 students. Data validity techniques through triangulation of sources and techniques. The data analysis technique uses stages of data condensation, data display, and conclusion drawing. The research results indicated that some students experienced conceptual difficulties. Apart from that, the lack of prerequisite knowledge is also a major factor in the difficulties experienced by students. This research provides a significant contribution in describing the understanding of Tadris mathematics students at UIN K.H. Abdurrahman Wahid Pekalongan relates the concept of abstract mathematics in depth